2005
DOI: 10.1038/sj.gene.6364225
|View full text |Cite
|
Sign up to set email alerts
|

Family-based association analysis implicates IL-4 in susceptibility to Kawasaki disease

Abstract: Several compelling lines of evidence suggest an important influence of genetic variation in susceptibility to Kawasaki disease (KD), an acute vasculitis that causes coronary artery aneurysms in children. We performed a family-based genotyping study to test for association between KD and 58 genes involved in cardiovascular disease and inflammation. By analysis of a cohort of 209 KD trios using the transmission disequilibrium test, we documented the asymmetric transmission of five alleles including the interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 54 publications
(46 reference statements)
1
58
0
1
Order By: Relevance
“…32 Burns et al 33 revealed that interleukin 4 has an important role in KD pathogenesis and disease susceptibility, but the results are different from the studies in the Taiwanese population. 34,35 The angiotensin-I-converting enzyme gene was reported to be associated with susceptibility to KD but not CAL formation in Taiwan, 36 and it was shown to be associated with the formation of severe coronary artery stenosis and myocardial ischemia in the Japan population.…”
Section: Discussionmentioning
confidence: 88%
“…32 Burns et al 33 revealed that interleukin 4 has an important role in KD pathogenesis and disease susceptibility, but the results are different from the studies in the Taiwanese population. 34,35 The angiotensin-I-converting enzyme gene was reported to be associated with susceptibility to KD but not CAL formation in Taiwan, 36 and it was shown to be associated with the formation of severe coronary artery stenosis and myocardial ischemia in the Japan population.…”
Section: Discussionmentioning
confidence: 88%
“…30 Although several other groups have studied other combinations of HLA subtypes, no consistent association has been detected so far. Considering that no significant linkage was detected near the 6p region in our genome-wide linkage analysis, 31 34 and MCP-1 35 ), hematopoietins (interleukin-4 (IL-4) [36][37][38] and IL-6 39 ), IL-1 family (IL-1b, 37 IL-18, 40 and IL-1Ra 37 ), IL-10 family (IL-10 41 ), platelet-derived growth factor family (vascular endothelial growth factor (VEGF) [42][43][44][45] and VEGFR2 42 ), and tumor necrosis factor (TNF) family (TNF-a, 46-50 lipoteichoic acid, 47 and CD40L 51,52 ). Other candidates include plasma proteins (C-reactive protein [53][54][55] and MBL2 53,55,56 ), matrix metalloproteinase (MMP) and their inhibitors (MMP2, 58 MMP3, 57,58 MMP-9, 58 MMP-12, 58 MMP-13, 58 and tissue inhibitors of metalloproteinase-2 59 ), enzymes related to atherosclerosis (methylenetetrahydrofolate reductase (MTHFR), 60 endothelial nitric oxide synthase, 61 and inducible nitric oxide synthase 61 ), components of the renin-angiotensin system (angiotensin-converting enzyme [62][63][64][65] and AGTR1 64 ), and an unclassified group (CD14, 66 FCGR2A, 67,68 SLC11A1, 69 PLA2G7, 70 UGT1A1, 71 MICA, 72 and HMOX1 71 ).…”
Section: Candidate Gene Approachmentioning
confidence: 88%
“…This triggered activation, in turn, starts a systemic immune response leading to uncontrolled inflammation and vasculitis in genetically susceptible patients (9)(10)(11). Although a number of previous studies have sought to determine the cause of this disease, very few have addressed the role of the different peripheral T-cell populations in the acute phase of KD or in the effectiveness of IVIG treatment (12,13).…”
mentioning
confidence: 99%